Funds Flow and Financial Control Analysis of the Student Financial Assistance Programs (StuFAP) - Victoria Catibog (Philippine Institute for Development Studies (PIDS), 2014)
This study presents the scholarship, grant-in-aid, and student loans (SGIAL) funds flow and its financial flow analysis and assesses the weaknesses and strengths of the SGIAL financial process. Some findings from the study show that the Department of Science and Technology (DOST) and the Commission on Higher Education (CHED) accounts and reports on SGIAL funds received from the General Appropriations Act (GAA) following standard government accounting rules and regulations deter scrupulous persons from misuse and misappropriation of the funds. However, administering scholarship funds has certain nuances that do not fit well with national procedures in the release of funds. For one, the fiscal year and the academic year do not jibe. DOST and CHED have to carefully consider this in their planning for the use of budgeted SGIAL funds from the GAA. The study recommends that there should be a creation of a scholarship trust fund to which releases from the GAA will be transferred. This will solve the problems caused by a nonsynchronized fiscal and academic year. It will also insure the availability of actual cash to pay entitlements of scholars on time. This also enables the agency implementing the scholarship program to have a better basis for planning and budgeting the funds allocated for the purpose that is released to it.
Keywords: I23; I28; 330; Commission on Higher Education (CHED); General Appropriations Act; scholarships; grants-in-aid (GIAs); student loans; Student Financial Assistance Programs (StuFAP); Department of Science and Technology (DOST); Priority Development Assistance Fund (PDAF)